Controlled micro-wrinkling of ultrathin indium-tin-oxide films for transparency tuning - Wei, Deyuan (2019)
Smart windows can electrically switch between clear and opaque states. Current smart windows based on polymer dispersed liquid crystal are expensive and they have moderate range of transparency tuning. Elastomeric tunable window devices are being researched as the low-cost alternates. They consist of a transparent elastomer substrate with surface electrodes that provide electrically controlled micro-wrinkling. They diffusely scatter the transmitted light and thus appear opaque when the surfaces are micro-wrinkled. On electrical activation the wrinkles are flattened, thus making the windows transparent like window blinds. However, the initial prototypes of these electrically tunable window devices showed limited transparency tuning because their transparent electrodes cannot be completely flattened. For example, the brownish e-beam evaporated indium-tin-oxide thin films (50 nm thick) remains mildly wrinkled (with 52.08% transmittance) even when subjected to 37% areal expansion, while its opaque state allows 39.14% transmittance. There is a need for more transparent thin-film electrode with better controllability of surface micro-wrinkling. This work reports a greatly improved tunable window device with enlarged range of transmittance tuning: a clear state of 71.5% transmittance and an opaque state of 2% transmittance. This new device made use of ultra-thin (6 nm) ITO thin films as the transparent compliant electrodes, which were initially wrinkled and can be flatten by 12.2% voltage-induced areal expansion. These ultra-thin ITO thin films are clearer with fewer thermally-induced wrinkles on the flat elastomer substrate (VHB 4905) as they were deposited at a lower surface growth temperature using the RF magnetron sputtering technique. In addition, they make compliant electrodes of higher electrical conductivity and can electrically unfold the mechanically induced micro-wrinkles by a small voltage-induced areal expansion (~12.2%). With the greatly enhanced performance, this electrically tunable window device is promising approach for low-cost smart windows.